Administrativno politicheskoye stroyeniye soyuza ssr (Государственное иедательство (ОГИЗ), 1930)
Diagram of different administrative structures in the USSR, with emblem of hammer and sickle and globe in the centre Original title: Административно политическое строение связи СССР. Suggested translation: Administrative-political structure of the USSR PO-0020